What Might Dewey Think of Knowledge Insertion?. Issue 4 (24th November 2020) - Obelleiro, Gonzalo
Abstract: In two articles, "Might Knowledge Be Insertable?" and "Is Knowledge Insertion Desirable?, " John Tillson argues that knowledge insertion is conceivable and desirable for the person who has it inserted. By knowledge insertion, he means the immediate or almost immediate acquisition of knowledge by means other than traditional processes of learning. He takes the case presented in the science fiction film The Matrix as paradigmatic and characterizes it as a special case of direct intervention, which begin with change in brain structure and function and result in in changes in thought patterns and behavior, by contrast to indirect interventions, which begin with changes in thought patterns and behavior and result in rewiring brain structure and functioning. Here, Gonzalo Obelleiro follows Tillson's argument and offers one special case in which knowledge insertion is not desirable and that is not fully elucidated by Tillson's conditions for desirability. John Dewey's notion of growth as summum bonum depends in important ways on gradual, progressive, traditional processes of learning. Deweyan growth constitutes a case of intrinsically valuable learning that can be tragically jeopardized by calculation errors in knowledge insertion. This is a significant risk that Tillson does not consider in his articles.